Reclamation of Jakarta Bay, Impoverishment and Marginalization of Fisherwomen: Case Study at Akuarium and Kamal Muara Village, Penjaringan - Wardhani, Endah (Yayasan Jurnal Perempuan, 2017)
It has been more than ten years since The Jakarta Bay reclamation project displaced fishermen from the sea where they were normally fishing. The direct impact of reclamation on fisherwomen was income decrease, because it has damaged the marine ecosystems due to the effects of sucking and backfilling of the sea sand. In addition, there will be at least 16,998 of fishermen households will be evicted from the coastal areas of Jakarta, Banten and Bekasi due to this reclamation. The findings of this study are: the reclamation made thefisherwomen become poorer, their burden is higher and they have experienced double marginalization. The research methodology is a qualitative study with feminist perspective. Data collection are by in-depth interview with ten fisherwomen, document study, and fieldsobservation. Selection of research sites is purposive, namely Kampung Akuarium and Kampung Kamal Muara, District of Penjaringan, North Jakarta Municipality. In particular, this study wants to bring up the voices of poor fisherwomen as marginalized group of people, who have not been heard. It is hoped they will be brave and voiced their rights and aspirations openly which they have not dared to do so.